2022
DOI: 10.1007/s00266-022-03100-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Piezosurgery and Conventional Osteotomies in Rhinoplasty on Post-Operative Oedema and Ecchymosis: A Systematic Review

Abstract: Piezosurgery use has become increasingly prevalent in osteotomies. Piezoelectric ultrasound waves can cut bone effectively, and some studies have shown reduced post-operative morbidities compared to conventional osteotomies. Oedema and ecchymosis are common complications of rhinoplasty and can impact patient satisfaction, wound healing, and recovery. We aim to provide an up-to-date comparison of post-operative oedema and ecchymosis in piezosurgery and conventional osteotomies. A literature search was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The utility of piezosurgical osteotomies for nasal osteotomies has been relatively well studied. Three recent systematic reviews [31 ▪▪ ] and metanalyses [32,33] comparing piezosurgery to conventional osteotomies in rhinoplasty found that the former was associated with less postoperative ecchymosis (namely periorbital ecchymosis), eyelid edema, and pain compared with conventional techniques. Reviews by Kisel et al [31 ▪▪ ] and Tsikopoulos et al [33] additionally found that piezoelectric osteotomies were associated with decreased overall mucosal injury (examined by either intraoperative or postoperative endoscopy) and postoperative pain.…”
Section: Rhinoplastymentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of piezosurgical osteotomies for nasal osteotomies has been relatively well studied. Three recent systematic reviews [31 ▪▪ ] and metanalyses [32,33] comparing piezosurgery to conventional osteotomies in rhinoplasty found that the former was associated with less postoperative ecchymosis (namely periorbital ecchymosis), eyelid edema, and pain compared with conventional techniques. Reviews by Kisel et al [31 ▪▪ ] and Tsikopoulos et al [33] additionally found that piezoelectric osteotomies were associated with decreased overall mucosal injury (examined by either intraoperative or postoperative endoscopy) and postoperative pain.…”
Section: Rhinoplastymentioning
confidence: 99%
“…Three recent systematic reviews [31 ▪▪ ] and metanalyses [32,33] comparing piezosurgery to conventional osteotomies in rhinoplasty found that the former was associated with less postoperative ecchymosis (namely periorbital ecchymosis), eyelid edema, and pain compared with conventional techniques. Reviews by Kisel et al [31 ▪▪ ] and Tsikopoulos et al [33] additionally found that piezoelectric osteotomies were associated with decreased overall mucosal injury (examined by either intraoperative or postoperative endoscopy) and postoperative pain. Prior studies have also compared long-term outcomes in nasal airflow, olfactory functions, and quality of life 8 weeks after surgery for patients that underwent rhinoplasty using piezoelectric versus conventional techniques.…”
Section: Rhinoplastymentioning
confidence: 99%